Mixed-dimensional PdSe2/SiNWA heterostructure based photovoltaic detectors for self-driven, broadband photodetection, infrared imaging and humidity sensing. Issue 7 (3rd February 2020) - Wu, Di; Jia, Cheng; Shi, Fenghua; Zeng, Longhui; Lin, Pei; Dong, Lin; Shi, Zhifeng; Tian, Yongtao; Li, Xinjian; Jie, Jiansheng
Abstract : A self-driven and broadband photodetector based on PdSe2 /SiNWA mixed-dimensional vdW heterojunction is fabricated, which shows a broadband spectrum from 200 nm to 4.6 μm with a high polarization sensitivity and good mid-infrared imaging capability. Abstract : The new discovery of two-dimensional (2D) palladium diselenide (PdSe2 ) films has attracted intensive research interest due to their unique asymmetric crystal structure and extraordinary optoelectronic properties, showing great potential for broadband and polarization photodetection. Herein, we have developed for the first time a self-driven, highly polarization-sensitive, broadband photovoltaic detector based on a PdSe2 /Si nanowire array (SiNWA) heterostructure. Owing to the strong light confinement effect of the SiNWA and broadband light absorption of PdSe2, the present device exhibits pronounced photovoltaic behavior and excellent performance in terms of a high responsivity of 726 mA W −1, a large specific detectivity of 3.19 × 10 14 Jones, an ultrabroad spectrum response range of 0.2–4.6 μm, and a fast response speed to monitor nanosecond pulsed light signals. Significantly, an impressive polarization sensitivity of 75 is achieved for the heterostructure device, which is among the highest for 2D material-based photodetectors. Thanks to the outstanding imaging capability, the detector can record images in both near infrared (NIR) and mid-infrared (MIR) ranges with a decent resolution. Moreover, the device exhibits light-enhanced humidity sensing behavior with a high sensitivity and a fast response/recovery time. Given these remarkable device features, the PdSe2 /SiNWA heterostructure will hold great promise for high-performance, polarization-sensitive broadband photodetection, infrared imaging and humidity sensing applications.